2016
DOI: 10.1007/s11085-016-9662-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase Investigations Under Steam Oxidation Process at 800 °C for 1000 h of Advanced Steels and Ni-Based Alloys

Abstract: During the test, no spallation of the external oxide scale was observed. The kinetic data showed that only the 263 alloy oxidized according to parabolic behaviour, whereas the other alloys deviated from the parabolic rate law, with time exponents of 0.4-0.6 or 0.3. Finally, cross-sectioned investigations of the exposed samples revealed that Ni-based alloys underwent extended internal oxidation, with the highest extent in HAYNES Ò 282 Ò reaching 25 lm and the lowest in HAYNES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 35 publications
1
13
4
Order By: Relevance
“…In addition, due to the formation of a thin oxide scale on Haynes Ò 230 Ò , the XRD pattern shown as well double carbides, g: Co 3 W 3 C and Co 6 W 6 C. In the 617 alloy instead of a MnCr 2 O 4 spinel, an NiCr 2 O 4 phase developed, since the 617 alloy showed no Mn concentration within the metal matrix. In comparison to the study performed at higher temperatures [6] only gamma-prime (c 0 ) strengthened Ni-based alloys showed a difference in phase development due to the lack of formation of TiO 2 and MnTiO 3 compounds. The Ni-based solid solution strengthened alloys developed the same phases as was reported in the work published earlier [6], despite 0.3 wt% Ti in the 617 alloy, no Ti containing phase was observed on XRD pattern.…”
Section: Xrd Analysescontrasting
confidence: 71%
See 4 more Smart Citations
“…In addition, due to the formation of a thin oxide scale on Haynes Ò 230 Ò , the XRD pattern shown as well double carbides, g: Co 3 W 3 C and Co 6 W 6 C. In the 617 alloy instead of a MnCr 2 O 4 spinel, an NiCr 2 O 4 phase developed, since the 617 alloy showed no Mn concentration within the metal matrix. In comparison to the study performed at higher temperatures [6] only gamma-prime (c 0 ) strengthened Ni-based alloys showed a difference in phase development due to the lack of formation of TiO 2 and MnTiO 3 compounds. The Ni-based solid solution strengthened alloys developed the same phases as was reported in the work published earlier [6], despite 0.3 wt% Ti in the 617 alloy, no Ti containing phase was observed on XRD pattern.…”
Section: Xrd Analysescontrasting
confidence: 71%
“…In comparison to the study performed at higher temperatures [6] only gamma-prime (c 0 ) strengthened Ni-based alloys showed a difference in phase development due to the lack of formation of TiO 2 and MnTiO 3 compounds. The Ni-based solid solution strengthened alloys developed the same phases as was reported in the work published earlier [6], despite 0.3 wt% Ti in the 617 alloy, no Ti containing phase was observed on XRD pattern. It is suggested that development of Ti containing phases is related strongly to concentration, activity, temperature and perhaps volume.…”
Section: Xrd Analysescontrasting
confidence: 71%
See 3 more Smart Citations